Upaya Pondok Pesantren dalam Membentuk Kepribadian Santri yang Tawadu di Pondok Pesantren Istifadah Bluto Sumenep - Shofi Yullah (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2023)
Pesantren holds a strong relationship with the teachings of Islam, where it nurtures the teachings of Islam driven by the founders, caregivers or people who lead them. It is the main media in spreading Islamic teachings to the community. It is thanks to pesantren that Islamic teachings can be grounded, understood and become a source of inspiration for the community in various aspects of life, both in the social, political, religious, and other fields. This paper will unravel and answer at least two main points: how does the efforts of the Pondok Pesantren Istifadah in Ging-Ging Sub-District Bluto Kab. Sumenep in the 2021/2022 academic year, strive to shape the personality of humble santri? And what are the implications for the formation of a humble santri personality? The approach used in this research is a qualitative approach, aimed at deciphering data, facts and various things obtained in the field, whether through observation, interviews, and documentation. From what is described above, it will come to the conclusion that the efforts of the Pondok Pesantren Istifadah shaping the personality of humble santri are pursued through moral education, recitation of the classical book, exemplary approach (uswah hasanah) and good advice model (mau'idhah hasanah). So from this, gradually the santri will have a humble personality, such as obedience to religious orders and teachers, respect and courtesy towards teachers and elders wherever and whenever they are. While the implications of efforts to form the personality of humble santri include: forming active and punctual santri, increasing the enthusiasm of santri in studying at madrasas, forming loyal and humble santri, and instilling mutual respect and appreciation in the midst of differences.